2007
DOI: 10.1007/s11096-007-9183-2
|View full text |Cite
|
Sign up to set email alerts
|

Psychological determinants of the intention to educate patients about benzodiazepines

Abstract: Objective General practitioners and pharmacists do not properly educate their patients about the disadvantages of benzodiazepines. In order to increase and improve education, this study will investigate which psychological factors (i.e., beliefs, outcome expectation, social norm and self-efficacy) predict the intention to educate. Methods A cross-sectional survey study was conducted in which 339 general practitioners and 149 pharmacists in the Netherlands completed a questionnaire. Results The Results show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 42 publications
0
22
0
Order By: Relevance
“…We retrieved the 52 studies from the original systematic review [8] reporting good psychometric properties and identified 20 new studies from the updated searches covering October 30, 2007 to October 31, 2010 [14], [15], [16], [17], [18], [19], [20], [21], [22], [23], [24], [25], [26], [27], [28], [29], [30], [31], [32], [33]. Our review included 72 studies [14], [15], [16], [17], [18], [19], [20], [21], [22], [23], [24], [25], [26], [27], [28], [29], [30], [31], [32], [33], [34], [35], [36], [37], [38], [39], [40], [41], [42], [43], [44], [45], [46], [47], [48], [49], [50], [51], [52], [53], [54], [55], [56]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We retrieved the 52 studies from the original systematic review [8] reporting good psychometric properties and identified 20 new studies from the updated searches covering October 30, 2007 to October 31, 2010 [14], [15], [16], [17], [18], [19], [20], [21], [22], [23], [24], [25], [26], [27], [28], [29], [30], [31], [32], [33]. Our review included 72 studies [14], [15], [16], [17], [18], [19], [20], [21], [22], [23], [24], [25], [26], [27], [28], [29], [30], [31], [32], [33], [34], [35], [36], [37], [38], [39], [40], [41], [42], [43], [44], [45], [46], [47], [48], [49], [50], [51], [52], [53], [54], [55], [56]…”
Section: Resultsmentioning
confidence: 99%
“…Our review included 72 studies [14], [15], [16], [17], [18], [19], [20], [21], [22], [23], [24], [25], [26], [27], [28], [29], [30], [31], [32], [33], [34], [35], [36], [37], [38], [39], [40], [41], [42], [43], [44], [45], [46], [47], [48], [49], [50], [51], [52], [53], [54], [55], [56], [57], [58], [59], [60], [61], [62], [63], [64], [65], [66], [67], [68], [69], [70], [71], [72], [73], [74], [75], [76], [77], [78], [79], [80], …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies involving community pharmacists have consistently reported higher counselling frequencies to patients receiving new prescriptions compared with those receiving long‐standing prescriptions [46]. Pharmacists have previously demonstrated low levels of both intended and actual patient education about benzodiazepine use [47]. Also concerning are patients' previous reports of receiving insufficient information on benzodiazepines[48,49] and varying engagement with pharmacists when having benzodiazepines dispensed [49]…”
Section: Discussionmentioning
confidence: 99%
“…This is important because while patients have previously shown low intentions[50] and a lack of willingness[51,52] to discontinue long‐term benzodiazepine use, it indicates that pharmacists may be able to raise the subject in a sizeable proportion of cases without an overtly negative reaction, and many patients may, in fact, be willing to heed their advice. This could help to dispel negative preconceptions that pharmacists may have regarding patients' responses to the suggestion of discontinuation, which is of importance as pharmacists have shown greater intentions to educate patients about benzodiazepines when anticipating positive outcomes [47]…”
Section: Discussionmentioning
confidence: 99%